EDUCATION COUNSELING AS AN EFFORT TO REDUCE STUNTING IN ALUH-ALUH DISTRICT, BANJAR REGENCY, SOUTH KALIMANTAN - Ermina Istiqomah; Sudjatmiko Setyobudihono; Abd Basid; Ary Nugraha; Noor Ridha Yanti; Rita Aprianti (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
The problem of stunting can be a factor inhibiting national development. A local wisdom-based approach is an important strategy to change people's behavior. The purpose of community service is to educate the community to know the potential of nutritious local food sources to prevent stunting. The service partners are Simpang Warga Dalam Village and Pemurus Village in Aluh-Aluh District which are recorded as one of the highest stunting loci in 2022 in Banjar Regency, South Kalimantan. Community service activities include counseling, training and mentoring from resource persons who understand local wisdom. The evaluation showed an increase in the value of knowledge and an increase in the ability of health cadres in carrying out measurement techniques and recording results. The enthusiasm of the participants was also shown by the many questions related to anemia, stunting and processing of local food ingredients